Transdisciplinarity in Mathematics Education Blurring Disciplinary Boundaries (Springer International Publishing, 2018)
The book explores various facets of transdisciplinarity in mathematics education and its importance for research and practice. The book comprehensively outlines the ways that mathematics interacts with different disciplines, world views, and contexts; these topics include: mathematics and the humanities, the complex nature of mathematics education, mathematics education and social contexts, and more. It is an invaluable resource for mathematics education students, researchers, and practitioners seeking to incorporate transdisciplinarity into their own practice.